The Effect of Good Corporate Governance, Company Size, Ownership Structure on Financial Performance in Food and Beverage Companies Listed on the Indonesia Stock Exchange 2010-2016 - Joel Simatupang (International Journal of Applied Finance and Business Studies, 2020)
This study aims to determine the effect of good corporate governance, size, managerial ownership of financial performance of food and beverage company in Indonesia stock exchange in the period 2010-2016. The study population of 17 companies. The sampling method used is purposive sampling method, in order to obtain a sample of 10 companies for 7 years of observation (2010-2016) with 70 observations (observation). Data were obtained from a sample of companies that are downloaded from the Indonesia Stock Exchange website. The data analysis technique used is descriptive statistical analysis and regression analysis. The process of data analysis done first is descriptive statistics, classical assumption test, multiple regression analysis and then test the hypothesis. The results of this study indicate the independent commissioner, audit committee, size and managerial ownership no partial effect of financial performance. While the result simultaneously the independent commissioner, audit committee, size and managerial ownership simultaneously of financial performance.